Intervensi Psikologis Pada Siswa Dengan Kesulitan Belajar (Disleksia, Disgrafia Dan Diskalkulia) - Sa’adati, Tatik Imadatus (STAI Miftahul Ula Nganjuk, 2015)
Psychological interventions can be used to assist in the education. One of the problems in is the achievement of learners are less than the maximum in field of education, even if they have a level of intelligence (IQ) in average/normal. Learning difficulties which is divided into difficulties/complicacy learning to read (dyslexia), difficulties learning process of writing (dysgraphia) and difficulty learning of math (dyscalculia) became one of the causes of the lack of student interest in learning and academic achievement of students is low. Learning methods for children with learning difficulties should suit/appropriate with studentsâ characteristics and the environment. In the domain of psychology, therapy or intervention for mentoring in the learning process also provides an important role for students. This review will discuss the psychological interventions for teachers and parents. Besides, the alternative intervention applicative psychomotor presented is Brain Gym that aims to improve childrens intelligence.